BESARAN PENGARUH MUTU PELAYANAN TERHADAP KEPUASAN PASIEN DI FASILITAS KESEHATAN: META ANALISIS - Diwian Jaya Putra, I Putu Okta; Laksmini, Putu Ayu; Semara Yanti, Ni Komang; Farmani, Putu Ika; Tunas, I Ketut (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2026)
The service operations of a health facility depend on patient satisfaction with the quality of service provided. Health care facilities must always look after the services provided to maintain good service quality. The result of an agency's service can be seen from 5 components, namely ‘SERVQUAL’. This research is a metaanalysis study that aims to measure the effect of the quality of service provided by health facilities on patient satisfaction. The data was obtained from 10 nationally reputable articles and analysed using the Review Manager (RevMan) 5.4.1 application. Based on the analysis conducted, it was found that all SERVQUAL components (Reliability, Responsiveness, Assurance, Empathy, Tangible) had the opportunity to generate patient satisfaction. The variable that has the greatest chance of producing patient satisfaction is empathy (Exp. B (OR) = 5.27; 3.34-8.31). Health care facilities are expected to maintain and pay attention to the quality of their services, both in terms of reliability, responsiveness, assurance, empathy, and physical evidence. For this reason, it is necessary to regularly evaluate and monitor all components owned by health service facilities to ensure that the quality of services implemented can meet the expectations of patients who come to visit.Keywords: Service Quality, Patient Satisfaction, Health Facility, Meta Analysis